PENGARUH PEMAHAMAN PAJAK, SISTEM PAJAK, DAN SIFAT MACHIAVELLIAN TERHADAP PERSEPSI WAJIB PAJAK TENTANG TAX AVOIDANCE - Siska Wulandari; Indra Cahya Setyawan (LPPM Universitas Bina Bangsa, 2022)
This study aims to analyze taxpayers' perceptions of tax avoidance. This study consists of three independent variables and one dependent variable. The independent variables in this study are tax understanding, tax administration system, and machiavellian nature. Meanwhile, the dependent variable is the taxpayer's perception of tax avoidance. This study uses a quantitative approach and the data used are primary data obtained from the dissemination of questionnaires. The population of this study is taxpayers in Bekasi Regency. The sample in this study was taxpayers in Cikarang. The total sample of 51 respondents and the sample that can be analyzed amounted to 50 respondents. Analysis of research data using descriptive analysis and multiple regression with the SPSS version 23 program. The results showed that partially, the tax administration system and the machiavellian nature did not affect the taxpayer's perception of tax avoidance because the test results were greater than the predetermined significant value, while knowledge and taxpayers' understanding had a positive effect on taxpayers' perceptions of tax avoidance. The limitation of this study is not to use variable types of sanctions and taxpayer compliance, so that it cannot be known the influence of these variables in providing opinions or perceptions about tax avoidance